(untitled) (Journal of Applied Oral Science, 2015)
Objective The benefit of the use of some intraoral devices in arthrogenous temporomandibular disorders (TMD) patients is still unknown. This study assessed the effectiveness of the partial use of intraoral devices and counseling in the management of patients with disc displacement with reduction (DDWR) and arthralgia.Materials and Methods A total of 60 DDWR and arthralgia patients were randomly divided into three groups: group I (n=20) wore anterior repositioning occlusal splints (ARS); group II (n=20) wore the Nociceptive Trigeminal Inhibition Clenching Suppression System devices (NTI-tss); and group III (n=20) only received counseling for behavioral changes and self-care (the control group). The first two groups also received counseling. Follow-ups were performed after 2 weeks, 6 weeks and 3 months. In these sessions, patients were evaluated by means of a visual analogue scale, pressure pain threshold (PPT) of the temporomandibular joint (TMJ), maximum range of motion and TMJ sounds. Possible adverse effects were also recorded, such as discomfort while using the device and occlusal changes. The results were analyzed with ANOVA, Tukey’s and Fisher Exact Test, with a significance level of 5%.Results Groups I and II showed improvement in pain intensity at the first follow-up. This progress was recorded only after 3 months in Group III. Group II showed an increased in joint sounds frequency. The PPT values, mandibular range of motion and the number of occlusal contacts did not change significantly.Conclusion The simultaneous use of intraoral devices (partial time) plus behavioral modifications seems to produce a more rapid pain improvement in patients with painful DDWR. The use of NTI-tss could increase TMJ sounds. Although intraoral devices with additional counseling should be considered for the management of painful DDWR, dentists should be aware of the possible side effects of the intraoral device’s design.